IN ENVIRONMENTAL POLLUTION, MEASURES TO REDUCE THE HARMFUL EFFECTS OF EMISSIONS FROM CARS - Kаmоlоvа Shаxnоzа Melibоevnа (Journals Park Publishing, 2024)
The vehicle as a result of the harmful effects human body and outlined recommendations to reduce the harmful effects of diseases are expressed in this article.